Effect of chelated trace minerals on nursery pig growth performance - Richert, B.T.; Kats, L.J.; Nuzback, D.E.; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 442 weanling pigs (initial age and wt of 22 d and 14.4 lb, respectively) was used on a commercial farm in northeast Kansas to evaluate growth performance with diets containing a chelated trace mineral premix or an inorganic trace mineral premix. Minerals evaluated in the premixes provided 16.5 ppm Cu, 165 ppm Fe, 40 ppm Mn, and 165 ppm Zn. For the inorganic trace mineral treatment, the mineral sources were copper sulfate, ferrous sulfate, manganous oxide, and zinc oxide. The chelated trace mineral premix had the following fractions of these minerals provided as amino acid chelates: 109.7% of Cu, 75.8% of Fe, 78.1% of Mn, and 47.0% of Zn with the balance coming from the previous inorganic sources to make diets similar in added trace mineral content. All diets also contained copper sulfate, providing an additional 188 ppm Cu. Pigs fed the chelated trace mineral had increased average daily gain (ADG), average daily feed intake (ADFI) , and lower feed efficiency (F/G) from d 0 to 7 postweaning. No differences occurred between treatments in ADG or ADFI from d 7 to 14. For this same period, pigs fed the inorganic trace minerals had lower F/G than pigs fed the chelated trace minerals. For the entire Phase I period (d 0 to 14), pigs fed the chelated trace minerals had greater ADFI with no difference in ADG or F/G. No differences occurred in ADG or FIG for the Phase II period (d 14 to 28). However, pigs fed the inorganic trace minerals had increased ADFI (P> .02). For the entire nursery period (d 0 to 28), no differences occurred in ADG, ADFI, and F/G between pigs fed either chelated or inorganic trace minerals. Based on the improved performance observed, chelated trace minerals may have been more available, which benefitted the weanling pig during the stressful first week postweaning. However, for the entire nursery period, based on this single study, no significant differences occurred in growth performance for pigs fed either trace mineral source.
Keywords: Swine; Starter; Minerals; Performance